Conceptualising soft power policy in Africa - Tazo, Ernest Teke (Graduate School of International Studies Ajou University, 2013)
Many years have passed since the 1960s when Africa began the transition to independent status. Despite this far, Africa have not had a glaring picture in the international stage because of many problems which included boundary conflicts. Boundary conflicts have dragged the continent behind for so many years. While Africa is trying to dabble with its problems, it image in the international arena have not been exhaustive. This research takes up the challenge to visit the causes of Africa’s boundary conflicts pacifically the case of Cameroon and Nigeria boundary conflict at the Bakassi peninsula bringing forth paradigm of a boundary conflict that was perfectly settled without resorting to violent conflict between the two powerful countries of the sub-region. My thesis will examine the use of hard power to resolve boundary conflicts as pursued by most other countries in Africa and it repercussion in comparism to the Cameroon soft power approach to settle its boundary conflict with Nigeria including the benefits that it has for the region as a whole. Keywords: Boundary conflict, hard power, repercussion, soft power
학위논문(석사)아주대학교 국제대학원 :국제개발협력과,2013. 8
Keywords: International Development; Cooperation